Postawy i stereotypy etniczne młodzieży akademickiej (polsko-niemieckie badania porównawcze) - Woźniak, Robert (Wydział Prawa i Administracji UAM, 1993)
The article discusses the opinions of the students in Poland and Germany, after the reunification of Germany. The sample contains the students of Berlin, Hamburg and Szczecin universities. The number of investigated persons was 423 (242 men and 181 women). In the study, a number of empirical research instruments have been used (e.g., a questionnaire of sociological investigation and a participant observation data analysis). The article focuses on three main problems: (1) basic theoretical and methodological concepts: (2) the acceptance among Polish and German students of the Odra-Nysa borderline (91.2% of the students accepted this borderline, though the figure was different in recent years); and (3) opinions about this borderline, as well as opinions of German students about social and economic situation in Poland.
Students' attitudes and the stereotypes of the nation (Polish-German comparatiue analysis)